Parental involvement and parenting style influence on children's learning and behavior - Hanafi, Zahyah; Nasaruddin, Mizuar (Universiti Utara Malaysia, 2005)
This study attempts to identify parental involvement (achievement values and discussion on school matters) and parenting style (demandingness and responsiveness) among parents in three selected schools and whether these factors influence children’s academic achievement and disciplinary behavior. Findings revealed that mothers had higher level of achievement values, discussion on school matters, demandingness, and responsiveness compared to fathers. Generally, mothers and fathers did not show any difference in their involvement and parenting style towards sons and daughters. Socio-economic status and parental involvement were only statistically correlated with academic achievement. On the other hand, socio-economic status and parenting style did not influence disciplinary behavior among children.